A structural view of ligand-dependent activation in thermoTRP channels - Steinberg, Ximena; Lespay-Rebolledo, Carolyne; Brauchi, Sebastian (Frontiers in Physiology, 2014)
Transient Receptor Potential (TRP) proteins are a large family of ion channels, grouped into seven sub-families. Although great advances have been made regarding the activation and modulation of TRP channel activity, detailed molecular mechanisms governing TRP channel gating are still needed. Sensitive to electric, chemical, mechanical, and thermal cues, TRP channels are tightly associated with the detection and integration of sensory input, emerging as a model to study the polymodal activation of ion channel proteins. Among TRP channels, the temperature-activated kind constitute a subgroup by itself, formed by Vanilloid receptors 1-4, Melastatin receptors 2, 4, 5 and 8, TRPC5, and TRPA1. Some of the so-called “thermoTRP” channels participate in the detection of noxious stimuli making them an interesting pharmacological target for the treatment of pain. However, the poor specificity of the compounds available in the market represents an important obstacle to overcome. Understanding the molecular mechanics underlying ligand-dependent modulation of TRP channels may help with the rational design of novel synthetic analgesics. The present review focuses on the structural basis of ligand-dependent activation of TRPV1 and TRPM8 channels. Special attention is drawn to the dissection of ligand-binding sites within TRPV1, PIP 2 -dependent modulation of TRP channels, and the structure of natural and synthetic ligands.